2023
DOI: 10.1159/000529182
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Metastasis as the First Manifestation of Hepatocellular Carcinoma: A Case Report

Abstract: Metastatic malignancies of the oral cavity are rare lesions, accounting for only 1–4% of all oral malignancies, and can occur in the jaw bones, the oral soft tissues, or even both. Although hepatocellular carcinoma is the most common primary hepatic tumor, no more than 1% of the cases show oral involvement. When metastatic tumor involves the oral cavity, the most frequent site is the posterior angle of the mandible. Histologically, hence, immunohistochemical markers are used for diagnosis. Glypican-3 and HepPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Commonly reported clinical findings in patients with a mandibular metastasis of HCC are those of a diffuse, firm and painless swelling in the temporal region [14], which are consistent with our patient. Additionally, symptoms including difficulty in opening of the mouth, numbness of the surrounding regions as well as toothache are observed [4,9,10,15,16]. Since there have been various reports of initial presentation of a metastatic HCC with a solitary orofacial metastasis [15,16], even more commonly than after an HCC diagnosis is established [9,16,17], we emphasize the need to consider this possibility in patients with known risk factors for HCC (liver cirrhosis, viral hepatitis and others).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Commonly reported clinical findings in patients with a mandibular metastasis of HCC are those of a diffuse, firm and painless swelling in the temporal region [14], which are consistent with our patient. Additionally, symptoms including difficulty in opening of the mouth, numbness of the surrounding regions as well as toothache are observed [4,9,10,15,16]. Since there have been various reports of initial presentation of a metastatic HCC with a solitary orofacial metastasis [15,16], even more commonly than after an HCC diagnosis is established [9,16,17], we emphasize the need to consider this possibility in patients with known risk factors for HCC (liver cirrhosis, viral hepatitis and others).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, symptoms including difficulty in opening of the mouth, numbness of the surrounding regions as well as toothache are observed [4,9,10,15,16]. Since there have been various reports of initial presentation of a metastatic HCC with a solitary orofacial metastasis [15,16], even more commonly than after an HCC diagnosis is established [9,16,17], we emphasize the need to consider this possibility in patients with known risk factors for HCC (liver cirrhosis, viral hepatitis and others). However, metastatic disease represents ~1% of all malignancies of the oral area [4].…”
Section: Discussionmentioning
confidence: 94%
“…For HCC, the discovery of GPC3 as a promising tumor-associated antigen because GPC3 is over-expressed in cancerous tissues and is significantly associated with poor prognostic disease-free survival and overall survival[ 67 , 68 ]. Indeed, clinical and basic studies have demonstrated that GPC3 is a carcino- embryonic proteoglycan anchored to the membrane of HCC cells and is involved in promoting HCC growth and invasion through a variety of signaling cascades; including the Wnt pathway, which plays a well-known role in embryogenesis[ 69 , 70 ]. It was found that the up-regulated expression of GPC3mRNA, gene or protein in the tissues or serum of patients with liver cancer could not only specifically diagnose liver cancer, but also had a bad prognosis with the patients with liver cancer[ 71 ].…”
Section: Hepatic Gpc3 Signallingmentioning
confidence: 99%